2010
DOI: 10.1063/1.3340977
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of single-walled carbon nanotube transistors after gamma radiation treatment

Abstract: Single-walled carbon nanotube field-effect transistors ͑CNT-FETs͒ were characterized before and after gamma radiation treatment using noise spectroscopy. The results obtained demonstrate that in long channel CNT-FETs with a length of 10 m the contribution of contact regions can be neglected. Moreover, radiation treatment with doses of 1 ϫ 10 6 and 2 ϫ 10 6 rad allows a considerable decrease parallel to the nanotube parasitic conductivity and even the shift region with maximal conductivity to the voltage range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…Exposure of up to 2 Mrad of γ radiation at a rate of nearly 10 3 rad/s resulted in a reduction in the transconductance of CNTFETs due to mobility degradation as a function of TID. 9 In contrast, another study 6 showed that the transconductance of CNTFETs and the level of noise did not change strongly after exposure to 1-2 Mrad of γ radiation at a rate of 10 2 rad/s. Exposure to 4.2 MeV α particles at a fl uence of 3 × 10 12 cm -2 reduced the conductivity of CNT papers, thin sheets of aggregated CNTs, by 25%.…”
Section: Introductionmentioning
confidence: 90%
“…Exposure of up to 2 Mrad of γ radiation at a rate of nearly 10 3 rad/s resulted in a reduction in the transconductance of CNTFETs due to mobility degradation as a function of TID. 9 In contrast, another study 6 showed that the transconductance of CNTFETs and the level of noise did not change strongly after exposure to 1-2 Mrad of γ radiation at a rate of 10 2 rad/s. Exposure to 4.2 MeV α particles at a fl uence of 3 × 10 12 cm -2 reduced the conductivity of CNT papers, thin sheets of aggregated CNTs, by 25%.…”
Section: Introductionmentioning
confidence: 90%
“…The results indicate that ionizing radiation can damage the crystalline lattice by creating defects, although the defect formation probability strongly depends on the energy, mass, and angle of the incident ionizing radiation. Recent studies which monitor the electronic transport properties of carbon-based FETs support these conclusions, that is, a high tolerance to proton irradiation (e.g., SWCNT-FETs [5,6], graphene-FETs [7]) or high-energy photon irradiation (e.g., SWCNT [8][9][10][11], graphene-FETs [12][13][14]), where the transport properties of the carbon nanostructures are maintained. However, the overall device response to irradiation is mixed.…”
Section: Introductionmentioning
confidence: 91%
“…A typical method for sterilizing materials is irradiation. To date there have been relatively few literature reports of the effect of irradiation in general on the properties of nanotube powders [10], films [11][12][13][14][15][16] or devices [15,16], and no reports of the effects on dispersed nanotubes. This information is most lacking in the case of the effects of a common sterilization procedure, gamma irradiation [17,18], as opposed to electron [19,20] or ion irradiation [11,14].…”
Section: Introductionmentioning
confidence: 98%